Effects of Localized Leg Muscle Vibration Timed to Gait Cycle Percentage during Overground Walking - Prado, Antonio; Agrawal, Sunil K. (Proceedings of the ... IEEE/RAS-EMBS International Conference on Biomedical Robotics and Biomechatronics, 2022)
Every movement requires the coordination of several muscles groups. Mechanosensors provide the necessary proprioceptive information to know the current state of the muscles, joints, and limb segments to perform motions successfully. The motor system activates the muscles accordingly to coordinate the joints according to the movement goals. Vibratory feedback can enhance the information sensed by the mechanosensors and affect the closed-loop locomotion control, thereby affecting the gait of a human user. This manuscript presents a comparison between two types of vibratory inputs at six different muscles: constant vibration of the muscles during the gait cycle and timed vibration synchronized to the percentage of the gait cycle. The results show that both vibratory strategies affect the gait of able-bodied subjects who participated in this study. The subjects modified their stride velocity and cadence. It is important to note that these gait characteristics depend on spatial and temporal parameters. However, what is unique that we found in this study is that constant vibration modified the spatial parameters, while timed vibration modified the temporal parameters.